2018
DOI: 10.1080/17461391.2018.1439104
|View full text |Cite
|
Sign up to set email alerts
|

Is international junior success a reliable predictor for international senior success in elite combat sports?

Abstract: Currently in the literature, there is a dearth of empirical research that confirms whether international junior success is a reliable predictor for future international senior success. Despite the uncertainty of the junior-senior relationship, federations and coaches still tend to use junior success as a predictor for long-term senior success. A range of former investigations utilising a retrospective lens has merely focused on success that athletes attained at junior level competitions. Success that was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
(34 reference statements)
2
27
0
3
Order By: Relevance
“…For this purpose, it is useful to apply models of prediction of sporting success, as is the case with this study. From the findings obtained, it can be inferred that the level of physical fitness shown in the junior category is an indicator of future sporting success, an idea previously suggested by other authors regarding combat sports 24 .…”
Section: Discussionsupporting
confidence: 54%
“…For this purpose, it is useful to apply models of prediction of sporting success, as is the case with this study. From the findings obtained, it can be inferred that the level of physical fitness shown in the junior category is an indicator of future sporting success, an idea previously suggested by other authors regarding combat sports 24 .…”
Section: Discussionsupporting
confidence: 54%
“…This is in line with studies in other sports such as combat sports, which showed that profiles of athletes become more specific as they grow older. 37…”
Section: Discussionmentioning
confidence: 99%
“…DA is used when groups are a priori known. Each subject (case) must have a score in one or more quantitative predictor measures, and a score on a group measure [28] Discriminant function analysis is a classification. The predictive model of a group membership according to the athlete`s level can be useful to rank athletes based on the selected parameters.…”
Section: Introductionmentioning
confidence: 99%